Culture and society: contemporary debates - Alexander, Jeffrey C.; Seidman, Steven (Cambridge Univ. Press, 1990)
The case for culture -- Approaches to culture: functionalist, semiotic, dramaturgical, Weberian, Durkheimian, Marxian, poststructuralist -- The place of religion : is modernity a secular or sacred order? -- The debate over the "end of ideology" : can secular reason create cultural order? -- Modernism or postmodernism : dissolution or reconstruction of moral order?